Study of the morbidity profile including depression among the elderly in the rural area, East Bangalore - Menzil, Margaret; R., Vinutha; S. K. Kallepalli, Swarna; Kamunuri, Ravikiran (International Journal Of Community Medicine And Public Health, 2024)
Background: Old age is associated with diminished physiological reserve; so any physical illness, metabolically derangement or pharmacological challenge can worsen cognitive and physical function. The only way to minimize or avoid these will be to be on the lookout and have a proactive approach and assessment in every older patient irrespective of the presenting complaint. This study aimed to assess the socio-demographic profile and self reported morbidity pattern of the elderly population and to estimate the prevalence of depression among the elderly population using the geriatric depression scale. Methods: A pre-designed, pretested and semi-structured questionnaire was used in the study. The data collection technique is by personal interview of the study subjects. A pre-designed, pretested and semi-structured questionnaire was used in the study. The data collection technique is by personal interview of the study subjects. Results: In our study more women were under depression than the men. The most common physical morbidity among the elderly population was cataract (59.7%), followed by arthritis (57.1%), non- specific body pains (40.1%) and hypertension (39%). Conclusions: Prevalence of depression among the elderly population is reported to be high (84.3%) in this study. Multi morbidity, socio economic factors and financial dependence were factors associated with depression in elderly.